PEMBUATAN SABUN TRANSPARAN BERBASIS MINYAK KELAPA DENGAN PENAMBAHAN EKSTRAK BUAH MENGKUDU (Morinda citrifolia) SEBAGAI BAHAN ANTIOKSIDAN - Lilis Sukeksi; Meirany Sianturi; Lionardo Setiawan (Jurnal Teknik Kimia USU, 2018)
The purpose of this study is to examine the effect of alkali concentration and the amount of added morinda citrifolia toward the formed of soap product. This study begins with maserating the noni fruit with ethanol. Then the making of transparent solid soap was made in the saponification process with a fixed variable oil volume of 70 ml, reaction temperature of 80 ° C and stirring time of 60 minutes. Whereas for the independent variables alkaline solution concentrations were 26%, 28%, 30%, 32%, the amount of noni extract 0 g, 10 g, 20 g, 30 g. The responses observed were water content, acidity (pH), saponification number, free alkali, free fatty acid, foam stability, surface tension and antioxidant activity. The best results were obtained at 26% alkaline concentration and 30 g of noni extract with a moisture content of 24,10%, 0% free alkali content, pH 9,0, free fatty acid content 0,480%, saponification 200 mg / g, surface tension 29,70 dyne / cm, foam stability 81% and antioxidant activity of 153,85 0µg / µL.